2020
DOI: 10.1302/1863-2548.14.200080
|View full text |Cite
|
Sign up to set email alerts
|

Probability analysis of sequential SCFE (PASS score)

Abstract: Purpose The study aimed to develop a scoring system based on clinical and radiological findings to predict the risk of a sequential slipped capital femoral epiphysis (SCFE). Methods Paediatric patients with unilateral SCFE and at least two years of radiographic follow-up were screened for inclusion. Medical records were reviewed for multiple variables including age, gender, body mass index (BMI), stability of SCFE, and time to sequential presentation. Radiographic analysis included triradiate physeal status, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…On the basis of these parameters, a Probability Analysis of Sequential SCFE (PASS score) was created. The amount of ≥3 points anticipates high risk of contralateral slip of above 28% [31]. This study suggests similarly to our findings that a thorough physical and radiological assessment of the patient and not a single radiological parameter should be considered before deciding on the prophylactic contralateral hip fixation [31].…”
Section: Discussionsupporting
confidence: 86%
“…On the basis of these parameters, a Probability Analysis of Sequential SCFE (PASS score) was created. The amount of ≥3 points anticipates high risk of contralateral slip of above 28% [31]. This study suggests similarly to our findings that a thorough physical and radiological assessment of the patient and not a single radiological parameter should be considered before deciding on the prophylactic contralateral hip fixation [31].…”
Section: Discussionsupporting
confidence: 86%
“…However, other studies have shown that the vast majority will develop a subsequent slip within 28 months. 1,8,9,11,27,28 This study did not present the natural history for the contralateral hip in children with a unilateral SCFE. Children were already selected from the initial study population, where a prophylactic fixation of the contralateral hip was performed.…”
Section: Strengths and Limitationsmentioning
confidence: 90%
“…25 Triradiate cartilage assessment for skeletal maturity as a predictor for a subsequent slip in the second hip has been advocated. 11,23,25,26 However, Danino et al 27 showed that triradiate status and Risser's grade did not influence their final multivariate analysis strength, but so did epiphyseal extension ratio, posterior epiphyseal angle and posterior sloping angle. When evaluating radiographs, the experience and the variation between clinicians must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding the status of the tri-radiate physis in SCFE patients has been primarily used when considering prophylactic fixation of the opposite hip when a patient with a unilateral SCFE presents. Popejoy et al [ 36 ] were instrumental in pointing this out, and the literature regarding the status of the tri-radiate physis in SCFE patients seems to concentrate solely on the consideration for prophylactic fixation of the opposite hip [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Our findings that the status of the tri-radiate physis in SCFE patients is also correlated with SCFE severity (LESA) is likely new and needs further corroboration from other centers.…”
Section: Discussionmentioning
confidence: 99%